2016
DOI: 10.1016/j.sjbs.2015.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of oral availability of ginseng fruit saponins by a proliposome delivery system containing sodium deoxycholate

Abstract: Ginseng fruit saponins (GFS) extracted from the ginseng fruit are the bioactive triterpenoid saponin components. The aim of the present study was to develop a drug delivery system called proliposome using sodium deoxycholate (NaDC) as a bile salt to improve the oral bioavailability of GFS in rats. The liposomes of GFS were prepared by a conventional ethanol injection and formed the solid proliposomes (P-GFS) using spray drying method on mannitol carriers. The formulation of P-GFS was optimized using the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…As well known, the potency of the ginseng extract is often measured by the percentage of contained ginsenosides. Total ginsenosides content of the ginseng extract may vary by species of ginseng, cultivation conditions, [22] method of processing and the part of the plant from which the extract is prepared [41].…”
Section: Sertoli Cells Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…As well known, the potency of the ginseng extract is often measured by the percentage of contained ginsenosides. Total ginsenosides content of the ginseng extract may vary by species of ginseng, cultivation conditions, [22] method of processing and the part of the plant from which the extract is prepared [41].…”
Section: Sertoli Cells Degenerationmentioning
confidence: 99%
“…The rationale of using nanoformulation of ginseng extract in the current study was to improve its pharmacokinetic properties since ginseng oral bioavailability is known to be very poor [22,41]. Oral bioavailability of ginseng can be enhanced by increasing the dose to saturate its metabolism or by changing its pharmaceutical formulation [22] such as nanoparticles formulation [23,43].…”
Section: Sertoli Cells Degenerationmentioning
confidence: 99%
“…We found that pretreatment with PNE (100 mg/kg) for 7 consecutive days before cerebral I/R could significantly decrease levels of proinflammatory cytokines, reduce the volume of brain infarcts, attenuate neurologic deficits, and maintain BDNF levels in the hippocampus even though exposure to each component of PNE was extremely low in the brains of normal and I/R rats. For herbal saponins, oral bioavailability is often limited owing to low membrane permeability, high molecular weight, fast clearance in the GI tract, and efflux transporters (Hao et al, 2016). Clinically, some commercial PNE formulations cure cerebral diseases mainly after intravenous administration, as exemplified by the Xue-Sai-Tong injection.…”
Section: Discussionmentioning
confidence: 99%
“…However, the apparent oil-water partition coefficient test ( Figure 7 ) showed that all of the six saponins had suitable liposolubility as far as druggability was concerned, with a K ow value between −2 and 1, and C1, C2, and C3 monomers also exhibiting good membrane permeability. Previously, the absolute oral bioavailability of C1 could be only calculated based on literature data [ 12 , 34 ], which yielded a low value. The permeability of the six saponin monomers decreased with an increase in the number of glycoside groups ( Figure 6 ), and pentacyclic triterpenoid saponins were investigated as a class of ingredients with poor oral bioavailability [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%